2020
DOI: 10.1002/hec.4025
|View full text |Cite
|
Sign up to set email alerts
|

Later retirement, job strain, and health: Evidence from the new State Pension age in the United Kingdom

Abstract: This paper examines the impact of raising the State Pension age on women's health. Exploiting a UK pension reform that increased women's State Pension age for up to 6 years since 2010, we show that raising the State Pension age leads to an increase of up to 12 percentage points in the probability of depressive symptoms, alongside an increase in self‐reported medically diagnosed depression among women in a lower occupational grade. Our results suggest that these effects are driven by prolonged exposure to high‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 64 publications
2
46
1
Order By: Relevance
“…About public policies, our data complement the accumulating evidence on the impact of pension reforms on health and mental health (Eibich, 2015 ; Carrino et al ., 2020 ), suggesting that older workers should be granted greater flexibility in the timing of retirement in order to reduce their mental burden and avoid the development of severe depression. As many countries are implementing budget reductions to social welfare (Hall and Soskice, 2001 ), it is crucial to retrieve solid evidence on how different retirement policies might impact healthy ageing to balance money saved from cuts to pension systems with direct and indirect costs passed onto healthcare and social support systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About public policies, our data complement the accumulating evidence on the impact of pension reforms on health and mental health (Eibich, 2015 ; Carrino et al ., 2020 ), suggesting that older workers should be granted greater flexibility in the timing of retirement in order to reduce their mental burden and avoid the development of severe depression. As many countries are implementing budget reductions to social welfare (Hall and Soskice, 2001 ), it is crucial to retrieve solid evidence on how different retirement policies might impact healthy ageing to balance money saved from cuts to pension systems with direct and indirect costs passed onto healthcare and social support systems.…”
Section: Discussionmentioning
confidence: 99%
“…These could include an increase in social support and in the time available for leisure and healthy activities, and disconnection from work-related stressors (Van Der Heide et al ., 2013 ; Eibich, 2015 ). These positive health effects were particularly observed among retirees from strenuous jobs (Belloni et al ., 2016 ; Blake and Garrouste, 2019 ; Ardito et al ., 2020 ; Carrino et al ., 2020 ; Fleischmann et al ., 2020 ). Therefore, as we reported in previous research (Vigezzi et al ., 2021 ), health behaviours changes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The final three studies in the review evaluated the effects of increasing the state retirement age (Atalay and Barrett, 2014;Carrino et al, 2020;Grip et al, 2012). Two of J o u r n a l P r e -p r o o f these studies focused on changes in retirement age for women (Atalay and Barrett, 2014;Carrino et al, 2020) whereas one study focused on changes for men (Grip et al, 2012).…”
Section: Delaying Retirement Benefits: Australia Netherlands and Uk mentioning
confidence: 99%
“…Using an IV approach, whereby different retirement age eligibility thresholds served as a proxies for retirement, the study found that retirement was associated with significant reductions in mental health problems in the overall sample (with regression coefficient of ß=-0.43, interpretation not provided, (p<0.01), and also a reduction in the lower income sample, concluding that increasing retirement age may have had significant adverse impacts on those affected and suggesting that inequalities may have also increased. Carrino et al (2020) evaluated the impact of a gradual increase in the state retirement age for women in the UK between 2010 and 2020. The study found that becoming ineligible for the state pension as a result of the reform had significantly increased the probability of depression among women aged 60-64 (by 6.2 pct points, p<0.05).…”
Section: Delaying Retirement Benefits: Australia Netherlands and Uk mentioning
confidence: 99%
“…For instance, research of recent date that has focused on the effects of increasing retirement ages shows the potential of looming social and economic inequalities at higher ages. The inequalities may be a result of the different health consequences [ 4 , 5 ] and the ability to cope with mental and physical challenges, especially in physically demanding jobs [ 6 ]. But the inequalities can also be generated by the lack of information or awareness of pending policy reforms.…”
Section: Introductionmentioning
confidence: 99%